High response photochromic films based on D–A diarylethenes and their application in holography. Issue 44 (13th July 2020) - Mantero, Maria Chiara; Oggioni, Luca; Pariani, Giorgio; Ortica, Fausto; Tosi, Silvano; Canepa, Maurizio; Bertarelli, Chiara; Tommasini, Matteo; Bianco, Andrea
Abstract : Photochromic diarylethenes with D–A structure are good candidates in holography thanks to their very large modulation of the complex refractive index. Abstract : A set of photochromic dithienylethenes bearing amino and nitro groups are synthesised and embedded at high concentrations in a polymer matrix (Cellulose Acetate Butyrate, CAB) to produce films showing a large reversible modulation of the complex refractive index in the Vis-NIR spectral range, thanks to an interesting combination of remarkable response at the molecular level and very high load capability in the chosen matrix. The photochromic derivatives are characterized in solution and in CAB films by means of electronic and vibrational spectroscopy, complemented by DFT calculations. Both the real and imaginary part of the refractive index are determined by spectroscopic ellipsometry. The modulation of the refractive index in the near infrared is in the range 0.02–0.04. These are very large values for such kinds of systems and they are due to a favourable combination of very large solubility of the derivatives in CAB and a high polarisability change. As for the change in transparency in the visible, contrast values larger than 10 3 are easily achieved. Based on such films, holograms are written and reconstructed with a very high fidelity and efficiency.